2020
DOI: 10.1051/bioconf/20202002002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tidal on Fe Distribution at Tidal Swamp Rice-Farming in Barito River Area, South Kalimantan, Indonesia

Abstract: Iron (Fe) poisoning can cause problems on growth, the formation of saplings, and the filling of grains. These problems lead to and plant death or decrease in productivity. The inhibition of growth and production is increasingly higher in susceptible varieties. The distribution of iron concentration varies in different regions and locations of swamp rice farming. Various adverse effects of iron poisoning on rice have been widely reported, but the spatial distribution of iron in tidal fields is still rare. Iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The AMMI-1 biplot (Figure 1) and the AMMI-2 biplot (Figure 2) revealed the inherent characteristics of the test environments for rice production, where E1 (alluvial peat swamp) represents the rich environments and E3 (lowland peat swamp) represents a poor environment. Alluvial soil is known to be rich in minerals and nutrients brought down by rivers and other bodies of water, which serves as a good crop soil (Mawardi et al, 2020), while peat soil has a low fertility level (Septiyana et al, 2017) and holds a variety of soil physical constraints (Herawati et al, 2021). Aside from the productivity difference, however, both environments emerged similarly weak in discriminating the rice genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The AMMI-1 biplot (Figure 1) and the AMMI-2 biplot (Figure 2) revealed the inherent characteristics of the test environments for rice production, where E1 (alluvial peat swamp) represents the rich environments and E3 (lowland peat swamp) represents a poor environment. Alluvial soil is known to be rich in minerals and nutrients brought down by rivers and other bodies of water, which serves as a good crop soil (Mawardi et al, 2020), while peat soil has a low fertility level (Septiyana et al, 2017) and holds a variety of soil physical constraints (Herawati et al, 2021). Aside from the productivity difference, however, both environments emerged similarly weak in discriminating the rice genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also assumed that the non-fulfillment of the number of nutrients N, P, K needed by plants is a factor in not reaching the potential yields in the INPARA 8 rice plant as described, and plant productivity will be hampered and conversely, with sufficient plant nutrient needs, plant growth and productivity will be better. Mawardi et al (2020) already reported that the productivity of rice planted in tidal soil is low, which was less than 2.5 Mg ha -1 .…”
Section: Grain Yield Per Hectarementioning
confidence: 96%
“…Rice production in a tidal swamp of Indonesia is relatively low (less than 2.5 Mg ha -1 ) (Mawardi et al 2020); it is lower than in irrigated paddy fields (Senewe and Alfons 2011). Low productivity is probably due to low soil fertility and high acidity of the soil combined with a high level of Exchangeable-Al (Imanudin and Armanto 2012), and the tidal soil contained sulfidic material called pyrite (Prasetyo et al 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The highest Fe concentration occurs in areas close to the in waterways. Rice seedling planting must reach a depth layer of more than 10 cm to produce optimal rice production (Mawardi et al, 2020). The characteristics of bronzing indicate iron toxicity in plants.…”
Section: Swamp In Indonesiamentioning
confidence: 99%